Compassion Fatigue of Addiction Counselor: Qualitative Study at Rehabilitation Center in Jambi - Siti Raudhoh; Ema Krisnawati (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
Talking about addiction rehabilitation, addiction counselor became one of the most important roles. Addiction counselors work full time and have big responsibility. The burden and responsibility they got, might lead them to experience a fatigue which is called compassion fatigue. It is exactly dangerous to the performance, personal life, and psychological well-being of the counselors. This research used qualitative research method with thematic analysis approach that aimed to get the description of compassion fatigue of the addiction counselors. The participants of this research were 4 addiction counselors in Jambi. The data collection technique used in this research was in-depth interview. In thematic analysis, the process of coding could produce theme lists and then those themes can be identified at the manifest level. The results showed that there were three components described in compassion fatigue of addiction counselor: symptom, risk factors, and protective factors. The addiction counselor showed some compassion fatigue in order of cognitive, emotional, and behavior domain. Being apathy, as in cognitive domain, was the strongest symptom among the others. Addictive counselor were at risk to suffer from compassion fatigue due to their experience worked as counselor, their experience as an addict—since mostly addictive counselor was an addict once—work stress, maladaptive coping strategies, unhealthy relationship, and their personal problem. Despite of the risks they face, the addictive counselors could still manage them and perform well with regard to the protective factors: adaptive coping strategies, self-development activity, work-environment, support system, and optimism.